Evolution of bacterial communities in the wheat crop rhizosphere - Donn, Suzanne; Kirkegaard, John A.; Perera, Geetha; Richardson, Alan E.; Watt, Michelle (Environmental microbiology, 2015)
Summary The gap between current average global wheat yields and that achievable through best agronomic management and crop genetics is large. This is notable in intensive wheat rotations which are widely used. Expectations are that this gap can be reduced by manipulating soil processes, especially those that involve microbial ecology. Cross‐year analysis of the soil microbiome in an intensive wheat cropping system revealed that rhizosphere bacteria changed much more than the bulk soil community. Dominant factors influencing populations included binding to roots, plant age, site and planting sequence. We demonstrated evolution of bacterial communities within the field rhizosphere. Early in the season, communities tightly bound to the root were simplest. These increased in diversity with plant age and senescence. Loosely bound communities also increased in diversity from vegetative to reproductive plant stages but were more stable than those tightly bound to roots. Planting sequence and, to a lesser extent, wheat genotype also significantly affected rhizosphere bacteria. Plasticity in the rhizosphere generated from crop root system management and genetics offers promise for manipulating the soil ecology of intense cereal systems. Analyses of soil microbiomes for the purpose of developing agronomic benefit should include roots as well as soil loosely adhered to the roots, and the bulk soil.